(untitled) (London Journal of Research In Science: Natural and Formal, 2024)
Mango (Mangifera indica) is one of the most popular tropical terrestrial fruit bearing plants. Different phytochemicals especially, polyphenols (specifically flavonoids), terpenoids, xanthones are present in sufficient amount in different parts of mango, so that mangos are considered as nutraceuticals in treatmentof different diseases. Among thousand varieties of mango, eight varieties are selected for our study from our college garden. Bioactive components from these unripe mangos have been extracted. The estimation of total phenolic content with these extracts shows that ‘himsagar’ variety of mango contains highest concentration of polyphenols in different pH and incubation time at 37°C. UV-spectrometric screening for flavonoids present in unripe mango pulp of ‘himsagar’, reveals that this specific variety of mango contains kaempferol-3-glucuronide. The presence of this phytochemical has been confirmed by the application of UV shift reagents such as NaOH, NaOAc, NaOH+ NaOAc and NaOAc +H3BO3 reagents. In-silico study with the compound kaempferol-3-glucuronide, identifies the aldehyde reductase (AKR1B1) as target protein for drug design for different diseases. This gene is expressed in increased amount in head and neck cancer cells compared to normal cells. From a pan-cancer point of view, this specific gene is also differentially expressed in twelve types of cancer cells. By using gene network analysis and molecular docking studies with target gene AKR1B1 and phytochemical kaempferol-3- glucuronide, present in unripe mango pulp, the efficacy of this flavonoid has been discussed elaborately for the treatment of various types of cancers.